1998
DOI: 10.1002/(sici)1099-0488(199812)36:17<3147::aid-polb14>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic polymer analogues

Abstract: Disordered fiber mats made of glass microfibers (GMF) were studied using small‐angle light scattering (SALS), ultrasmall‐angle X‐ray scattering (USAXS), SEM, and optical microscopy. The morphological scaling of these materials in the micron scale was very similar to that of polymers in the nanometer scale. In some fiber mats, such as GMF, the structure is randomized at the time of formation, leading to a statistical analogy with the thermal randomization that occurs in nanometer‐scale, high polymers. Analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Scattering measurements provide a means to quantify the fractions and sizes of morphological units. Extensive small-angle X-ray scattering (SAXS) studies have been conducted to follow structural changes during crystallization and melting of EOCs. ,, These studies have demonstrated the importance of SAXS for understanding thermodynamic and kinetic factors affecting the development the lamellar (nanoscale) morphology of semicrystalline polymers. Scattering data at very small angles, possible with ultra small-angle X-ray scattering or small-angle light scattering (SALS), is necessary to investigate the spatial arrangement of micrometer crystalline aggregates or superstructures. Some recent studies ,− have demonstrated that time-resolved, polarization dependent SALS is very sensitive to micrometer scale density and orientation fluctuations arising during polymer crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Scattering measurements provide a means to quantify the fractions and sizes of morphological units. Extensive small-angle X-ray scattering (SAXS) studies have been conducted to follow structural changes during crystallization and melting of EOCs. ,, These studies have demonstrated the importance of SAXS for understanding thermodynamic and kinetic factors affecting the development the lamellar (nanoscale) morphology of semicrystalline polymers. Scattering data at very small angles, possible with ultra small-angle X-ray scattering or small-angle light scattering (SALS), is necessary to investigate the spatial arrangement of micrometer crystalline aggregates or superstructures. Some recent studies ,− have demonstrated that time-resolved, polarization dependent SALS is very sensitive to micrometer scale density and orientation fluctuations arising during polymer crystallization.…”
Section: Introductionmentioning
confidence: 99%